Rapid corrosion rates and high mechanical properties of as-extruded Mg–Er–Ni alloys by introducing LPSO and γʹ phases - Chaoneng Dai; Sanlue Pei; Kai Ma; Ye Wang; Danqian Wang; Jinxing Wang; Yanlong Ma; Jingfeng Wang (Journal of Materials Research and Technology, 2023)
The Mg–Er–Ni alloy with comparable strength and solubility was prepared by controlling the Ni content. The mechanical properties and corrosion mechanism of alloys with long-period stacking ordered (LPSO) phase, as well as those with both LPSO and γʹ phases, were investigated and clarified. This study focused on investigating the underlying reasons for the high mechanical strength and fast corrosion rate of the Mg–13Er–3Ni alloy with LPSO and γʹ phases. The highest corrosion rate of the Mg–13Er–3Ni (wt.%) alloy is not only associated with the high volume fraction of the LPSO phase, which provides a larger zone for the corrosion cathode rather than forming a corrosion barrier, but also linked to the introduction of the γʹ phase that forms new sites for galvanic corrosion and avoids the formation the Er2O3 corrosion product film with corrosion-resistant. Moreover, The high mechanical properties of Mg–13Er–3Ni alloy are mainly attributed to the texture strengthening, dislocation strengthening and the second phase reinforcement that were caused by high volume fraction of LPSO phase and the precipitation of lamellar γʹ phase in Mg matrix. Generally, Compared to the Mg–13Er-1.5Ni (wt.%) alloy, the corrosion rates and mechanical strength of Mg–13Er–3Ni (wt.%) alloy were increased significantly by 302.8% and 50.3%, respectively, by coupling the LPSO and γʹ phases. Its ultimate tensile strength of 445 MPa and corrosion rare of 128.5 mg cm−2 h−1, which provides a new high strength and rapid corrosion Mg alloy materials for fracturing tools application.